The dark wives - Cleeves, Ann (2024)
"As New York Times bestseller Ann Cleeves's beloved Vera series explodes in popularity in print and on TV, this stunning eleventh book explores the web of secrets surrounding a young man's death. The man's body is found in the early morning light by a local dog walker in the park outside Rosebank, a home for troubled teens in the coastal village of Longwater. The victim is Josh, a staff member, who was due to work the previous night but never showed up. DI Vera Stanhope is called out to investigate the death, with her only clue being the disappearance of one of the home's residents, fourteen-year-old Chloe Spence. Vera can't bring herself to believe that a teenager is responsible for the murder, but even she can't dismiss the possibility. Vera, Joe and new team member Rosie Bell, are soon embroiled in the case, and when a second connected body is found near the Three Dark Wives monument in the wilds of the Northumberland countryside, superstition and folklore begin to collide with fact. Vera knows she has to find Chloe to get to the truth, and the dark secrets in their community that may be far more dangerous than she could have ever believed possible"--
Keywords: Detective and mystery fiction; Novels